Working by projects: a way to enrich critical thinking and the writing process in a third grade eflclassroom - Ruiz, Sandra Dolores (Colombian Applied Linguistics Journal, 2013)
This document presents the result of a qualitative action research developed with thirty-three third grade students at a public school in Bogota. This action research aimed at describing and analyzing the role of project work in the development of critical thinking in third grade EFL students and to describe and document the way in which those students developed their writing skills through this methodology. The participants developed different inquiries related to topics they were interested in exploring and related to the recycling project of the school. The data were collected during eleven sessions carried out along eight months through field notes, artifacts, and audio recordings. The results show that through project work the students enhanced their emerging critical thinking skills and their writing process; improved their interactions with their classmates, discovered that learning English was something useful for their lives, and therefore they acquired more confidence in writing and speaking in English. Additionally, they became more reflective, organized and critical about what they think, what they say, and about what happens around them.